Pre-operative and 24 hourPost-operation Changes of Peak Expiratory Flow RatePrediction Post-operation Pulmonary Complications - Boonnuch, Wiroon (Siriraj Medical Journal, 2015)
Background: Post-operative pulmonary complications (PPCs) are common problems after abdominal operations. The incidence varies from 10 to 69% for atelectasis and 9 to 40% for post-operation pneumonia. Many studies have investigated risk factors and risk indices for predicting PPCs. However, no definite predictors for PPCs have yet been described. Objective: To develop a simple, reliable, and safe diagnostic tool for early detection of post-operation pulmonary complications. Methods: A series of 151 consecutive patients scheduled for elective abdominal operations were studied between 1 September 2003 and 31 August 2004 at The Department of Surgery, Faculty of Medicine at Siriraj Hospital. The patients were measured for peak expiratory flow rate (PEFR) a night before operation, followed by every 24 hr post-operation. The data was analyzed using univariate and multivariate regression analyses with respect to post-operation pulmonary complications. Results: A total of 15 patients (9.9%) developed post-operation pulmonary complications. Univariate analysis demonstrated that preoperative PEFR (PrePEFR) and 24 hr post-operation PEFR (PostPEFR) could predict PPCs. Using multivariate regression analyses, the PEFR Score was developed and calculated as (17.24 х Malignant)-(0.16 х PostPEFR). A cut point value was -4.68. The diagnostic sensitivity was 80% and specificity was 73.5%. Conclusion: 24 hours post-operation PEFR is a simple and valuable bedside method for predicting PPCs. Keywords: Peak expiratory flow rate, post-operative pulmonary complications